Extensive introgression and mosaic genomes of Mediterranean endemic lizards - Weizhao Yang; Nathalie Feiner; Catarina Pinho; Geoffrey M. While; Antigoni Kaliontzopoulou; D. James Harris; Daniele Salvi; Tobias Uller (Nature Communications, 2021)
Islands can provide insights into the evolution of diverse adaptations. The genomes of 34 major lineages of Mediterranean wall lizards reveal a highly reticulated pattern of evolution across the group, characterised by mosaic genomes and showing that hybrid lineages gave rise to several extant endemics.